Lignin-based nanoencapsulation for sustainable herbicide delivery: controlled release and bioactivity of 2,4-D and MCPA compared to commercial formulations - Somayeh Ghaffari Ganzagh; Ali Reza Yousefi; Abbas Rahdar; Mehdi Mohammadi (Scientific Reports)
Abstract Herbicides are the extensively used class of pesticides, which beside the active ingredient, in their formulation accompanying substances such as emulsifiers, surfactants and others is needed. The potential toxicity of these synthetic chemicals could pose serious risks to the human health, nontarget organism and environment. In this work we developed biodegradable lignin nanoparticles (LNPs) as environmentally friendly and controlled release carriers of 2,4-dichlorophenoxyacetic acid 2,4-D and 2-methyl-4-chlorophenoxyacetic acid MCPA. LNPs were synthesized via solvent-free nanoprecipitation, achieving high entrapment efficiencies of 90.7% (2,4-D) and 97.4% (MCPA), confirmed by ultraviolet–visible spectroscopy. In vitro release studies revealed sustained herbicide release in buffer solutions (pH 5.5–7.5), with 68–74% release over 72 h, compared to rapid release from commercial formulations. Bioactivity assays of on Descurainia sophia showed that LNP-encapsulated formulation of herbicides reduced weed dry weight by 62.31% and density by 56.09% compared to untreated controls, statistically matching the weed control efficacy of commercial formulations. Field trials further validated these results. LNP-encapsulated 2,4-D + MCPA reduced Amaranthus blitoides dry weight by 91.10% and density by 65.09%, while this new formulation decreased Chenopodium album dry weight and density by 96.01% and by 66.75%, respectively. Notably, lignin’s inherent biodegradability and non-toxic nature provide a sustainable alternative to conventional synthetic adjuvants, significantly reducing the risks of environmental contamination. Our study highlights the potential of lignin-based nanoencapsulation to preserve weed control efficacy while promoting environmentally friendly and safer herbicide formulations.